The impact of R&D resources and capability on company performance - Sofian, Saudah (Penerbit UTM Press, 2014)
R&D resources and capability is expected to affect company performance, especially those of high technology. Highlights of the work shows companies with high R&D expenditure and manpower resources typically influence company performance. Therefore, in order to improve the company's performance it is important to take into account the elements of R&D resources and capability. Given the fact that these elements are important to the technology-based companies, this study was conducted to examine whether R&D resources and capability influence business performance. A set of questionnaire was distributed among 138 technology-based companies and statistical analyses were employed to analyze gathered data from the survey. Findings indicate that the elements do influence the business performance of the companies.